PENGARUH KECEPATAN ANGIN DAN VARIASI JUMLAH SUDU TERHADAP UNJUK KERJA TURBIN ANGIN POROS HORIZONTAL - Aryanto, Firman; Mara, Made; Nuarsa, Made (Universitas Mataram, 2013)
The wind turbine is a device that converts wind energy into mechanical energy and then converted into electrical energy through a generator. Horizontal axis wind turbines can increase the efficiency to get the maximum power coefficient. One was using the blade numerous. Maximum efisiensi system will increase the number of watts (power) generated so as to obtain a certain number of watts by simply using the number of windmills lessThe object of this research is the performance testing horizontal axis wind turbine with wind speed variation and variation in terms of the number of blade Efisiensi system (? ) and Tip Speed Ratio (TSR). Research conducted with the wind coming from the source to the Wind Tunnel fan to direct wind. Wind speed is used there are three variations of the 3 m/s, 3.5 m/s, and 4 m/s and varying the amount of blade that is 3, 4, 5 and 6 blade.The results showed that the best ? values obtained at a maximum wind speed of 4 m / s and the number of blade 5 with a value of 3.07% ?, whereas ? smallest value obtained at wind speeds of 3 m/s and the number of blade 3 that the value of 0.05% ?. For TSR maximum value at a maximum speed of 4 m/s occurred in the number of blade 5 is equal to λ = 2.11, while the lowest value at wind speeds of 3 m/s resulting in blade number 3 is equal to λ = 1.49.